Ethnopharmacology, phytochemistry and pharmacology of the genus Hedyosmum (Chlorantaceae): A review. (15th November 2019) - Radice, Matteo; Tasambay, Angélica; Pérez, Amaury; Diéguez-Santana, Karel; Sacchetti, Gianni; Buso, Piergiacomo; Buzzi, Raissa; Vertuani, Silvia; Manfredini, Stefano; Baldisserotto, Anna
Abstract: Ethnopharmacological relevance: The genus Hedyosmum (family: Chloranthaceae) represents an interesting source of natural active compounds, and the 45 species of this genus are widespread in Central and South America and to a lesser extent Southeast Asia (southern China and western Malaysia). Several species are traditionally used in folk medicine. However, the data made available in recent years have not been organized and compared. Aim of this review: The present study is a critical assessment of the state-of-the-art concerning the traditional uses, the phytochemistry and the pharmacology of species belonging to the genus Hedyosmum to suggest further research strategies and to facilitate the exploitation of the therapeutic potential of Hedyosmum species for the treatment of human disorders. Materials and methods: The present review consists of a systematic overview of scientific literature concerning the genus Hedyosmum published between 1965 and 2018. Moreover, an older text, dated from 1843, concerning the traditional uses of H. bonplandianum Kunth has also been considered. Several databases (Francis & Taylor, Google Scholar, PubMed, SciELO, SciFinder, Springer, Wiley, and The Plant List Database) have been used to perform this work. Results: Sixteen species of the genus Hedyosmum have been mentioned as traditional remedies, and a large number of ethnomedicinal uses, including for the treatment of pain, depression, migraine, stomach-ache and ovary diseases, have been reported. Five species have been used as flavouring agents, tea substitutes or foods. Sesterterpenes, sesquiterpene lactones, monoterpenes, hydroxycinnamic acid derivatives, flavonoids, and neolignans have been reported as the most important compounds in these species. Studies concerning their biological activities have shown that members of the Hedyosmum genus possesses promising biological properties, such as analgesic, antinociceptive, antidepressant, anxiolytic, sedative, and hypnotic effects. Preliminary studies concerning the antibacterial, antioxidant, antiplasmodial, and antifungal activities of these plants as well as their cytotoxic activities against different tumour cell lines have been reported. Some active compounds from the Hedyosmum genus have been used as starting points for the innovative and bioinspired development of synthetic molecules. A critical assessment of these papers has been performed, and some conceptual and methodological problems have been identified regarding the materials and methods and the experimental design used in these studies, including a lack of ethnopharmacological research. Conclusions: The present review partially confirms the basis for some of the traditional uses of Hedyosmum species (mainly H. brasiliense ) through preclinical studies that demonstrated their antinociceptive and neuroprotective effects. Due to promising preliminary results, further studies should be conducted on 13-hydroxy-8, 9-dehydroshizukanolide and podoandin. Moreover, several essential oils (EOs) from this genus have been preliminarily investigated, and the cytotoxic and antibacterial activities of H. brasiliense and H. sprucei EOs certainly deserve further investigation. From the promising findings of the present analysis, we can affirm that this genus deserves further research from ethnopharmacological and toxicological perspectives. Graphical abstract: Image 1